Asuhan Kebidanan Komprehensif Pada Ny.N Umur 20 Tahun G1P0A0 Dengan Tinggi Badan 142 cm Di Wilayah Kerja Puskesmas Bantarkawung Tahun 2024 - Depi Yuidi Aningsih; Endang susilowati; Mupliha Mupliha (Inovasi Kesehatan Global, 2026)
A high-risk pregnancy is a pregnancy that can affect both the pregnancy, delivery, newborn, and postpartum period. There are several high-risk pregnancies, including pregnant women who are <145cm tall, have low birth weight, are too young, and give birth too closely spaced, or what is known as the 4T. Prevention is carried out by conducting comprehensive supervision, this is a way to reduce MMR and IMR. The Central Java government has developed the One Student One Client (OSOC) program, it is hoped that the implementation of this program can reduce MMR in Central Java. MMR according to WHO in 2023 reached 189/100,000 live births, MMR based on ASEAN reached 235/100,000 live births, MMR according to the Indonesian Ministry of Health reached 205/100,000 live births, MMR in Central Java in 2023 has reached 485/100,000 live births, MMR in Brebes in 2023 54/100,000 live births and at the Bantarkawung Community Health Center MMR in 2023 amounted to 2 cases of maternal death. In this study, researchers used Varney and SOAP to document midwifery care comprehensively, with direct qualitative descriptive approach methods such as observation, interviews, and documentation.